Buyer-seller conflict and cooperation in marketing channels: port wine distribution - Crespo de Carvalho, J.; Sequeira, L. (International Journal of Wine Reasearch, 2013)
The main purpose of this study is to research buyer-seller conflict and cooperation in distribution channels. Based on a multidimensional case study, eight research hypotheses were formulated. Some quantitative research was conducted, based on a questionnaire sent to 101 port wine producers and distribution companies (61 answered properly – 31 producers and 29 distributors – which gave the authors a 60% rate of response, considered to be very good for these types of studies; those 101 port wine producers and distributors initially chosen were the most important in Europe, considering the volume of production and sales, and constituting, for that reason, a convenience sample). A binary probit model was developed to analyze the data. The results of the study demonstrate that when conflict is ongoing and intense it prevents the development of cooperative relationships. A trustworthy company is more likely to solve conflicts. When trust and adaptation capabilities increase, so does potential cooperation. The results also show that the presence of a foreign sales representative in the team does not exert a negative influence on cooperation. Finally, cooperation can be considered as an important means of developing skills and resources, which can then be applied to existing transaction relationships.